Strategic management of internal employer branding – guerilla strategies to engage and retain top employees in a challenging workforce environment - Barbulescu, Florentina-Mihaela; Vasiluță-Ștefănescu, Marius; Stoicov, Ionela; Coman, Claudiu; Coman, Ecaterina (Frontiers in Communication, 2024)
In a globalized and constantly evolving employment environment, it is imperative that organizations cultivate effective employer branding strategies to maintain competitiveness and attractiveness. These would allow them to obtain unique advantages in the market but also support for the internal employer brand. Despite the critical role of employer branding in attracting and retaining top talent, there remains a gap in understanding its relationship to HRM practices and employee perceptions of those practices. The purpose of this research was to investigate the correlation between human resources management practices and employer branding measured through organizational attractiveness and seen from the employees' perspective. Additionally, to find out if there is a significant difference between the private and public sector in terms of the perception of HRM practices influencing organizational attractiveness. In this regard, a questionnaire was applied to 800 respondents, employed in various positions in private and public sector organizations in western Romania. Two scales were applied to evaluate human resources management practices and the employer's attractiveness from the employees' perspective. Findings indicate a direct and positive relation between HRM practices and organizational attractiveness, with particular emphasis on performance appraisal practice, training and development, and work-life balance practices. When it comes to private sector, the significant practices influencing organizational attractiveness are performance appraisal, safety, and work-life balance practices, whereas in the public sector we have training-development and performance appraisal practices. These results underline the role of human resource management in strengthening internal support for the employer brand and increasing overall employer attractiveness.